PENGARUH LATIHAN KEKUATAN OTOT LENGAN TERHADAP KEMAMPUAN PASING ATAS DALAM PERMAINAN BOLA VOLI SISWA SMA NEGERI 3 TONDANO - Sondakh, Nofrie; Ompi, Serli (Yayasan Syalom Cipta Sumikolah, 2024)
The problem in this study is Is there an Effect of Arm Muscle Strength Training on Upper Passing Ability in the Volleyball Game of SMA Negeri 3 Tondano Students? Research Objective: to find out how much influence arm muscle strength training has on upper pasing ability in volleyball games of SMA Negeri 3 Tondano students? Research Hypothesis: There is an Effect of Arm Muscle Strength Training on Upper Lifting Ability in the Volleyball Game of SMA Negeri 3 Tondano Students. The research method used is an experimental method with treatment in the form of exercises given for eight weeks. The population in this study is all female class X students totaling 72 people and a sample of 20 people, then divided into 2 groups by lottery that got an odd number is the experimental group and the one who gets an even number is the control group. Data collection instrument: Upper Passing Test. The research design used: randomized control groups pre-test and post-test design. The hypothesis test uses statistical techniques with the t-test. The results of hypothesis analysis obtained t observations worth 15,546 while t tables obtained from the degree of freedom n-1 + n2 – 2 are 10 + 10 – 2 = 18 and the level of confidence = 0.05 is 2,101. According to the test criteria, accept Ho if t observation is smaller than t table and reject Ho if t observation is greater than t table. Because t observations are greater than t tables, the results of the analysis show rejection of Ho and acceptance of Ha. Research conclusion: there is an effect of arm muscle strength training on upper passing ability in volleyball games of SMA Negeri 3 Tondano students